The Impact of Internal CSR towards Employee Engagement and Affective Commitment in XYZ Hotel Surabaya - Santoso, Irene Listyani (iBuss Management, 2014)
Employees as one of the business partners play an important role to increase companyâs performance. By having good employeesâ performance on work will impact the short-term and long-term result of the business. This phenomenon happens when the employees basically engage and committed with their company. The greater the engagement and commitment employees have, the greater their willingness to go extra mile and deliver excellent performance. They will be also satisfied and proud to be a part of the company. This study aims to analyze the impact of internal Corporate Social Responsibility (CSR) which are training and education, health and safety, human rights, work-life balance, as well as workplace diversity on employee engagement and affective commitment. Data was gathered from 90 employees in XYZ Hotel SurabayaÂ  by using simple random samplingÂ  and multiple regression analysis was utilized as the analytical tool. The result showed that health and safety was the strong predictor in effecting both employee engagement and affective commitment. Â Keywords: Employee, internal CSR, employee engagement, affective commitment